a formula for the general term a n of the sequence assuming the pattern of the first few terms continues. { − 13/3 , 16/9 , − 19/27 , 22/81 , − 25/243 , ... } is [tex](-1)^n\frac{13+3(n-1)}{3^n}[/tex] .
Step-by-step explanation:
Here we have , the pattern of the first few terms continues. { − 13/3 , 16/9 , − 19/27 , 22/81 , − 25/243 , ... } . We need to find a formula for the general term a n of the sequence . Let's find out:
In this question there is no such technique , instead we have to use our brain to manipulate the pattern as :
1st term = − 13/3 = [tex](-1)^1\frac{13 }{3^{1}}[/tex]
2nd term = 16/9 = [tex](-1)^2\frac{13+3(1)}{3^2}[/tex]
3rd term = − 19/27 = [tex](-1)^3\frac{13+3(2)}{3^3}[/tex]
4th term = 22/81 = [tex](-1)^4\frac{13+3(3)}{3^4}[/tex]
5th term = − 25/243 = [tex](-1)^5\frac{13+3(4)}{3^5}[/tex]
nth term = [tex](-1)^n\frac{13+3(n-1)}{3^n}[/tex]
Therefore, a formula for the general term a n of the sequence assuming the pattern of the first few terms continues. { − 13/3 , 16/9 , − 19/27 , 22/81 , − 25/243 , ... } is [tex](-1)^n\frac{13+3(n-1)}{3^n}[/tex] .